Effects of oxygen supplementation in autonomic nervous system function during exercise in patients with idiopathic pulmonary fibrosis and exertional desaturation. (29th June 2021) - Boutou, Afroditi K.; Dipla, Konstantina; Theodorakopoulou, Marieta P.; Markopoulou, Katerina; Pitsiou, Georgia; Papadopoulos, Stavros; Kritikou, Stella; Stanopoulos, Ioannis; Zafeiridis, Andreas
Abstract: Introduction: Patients with idiopathic pulmonary fibrosis (IPF) have reduced exercise capacity and often present exertional dyspnea and desaturation. The role of autonomic nervous system (ANS) as a pathogenetic contributor to this dysfunction has not been evaluated. Objective: To evaluate whether improvement of arterial oxygen saturation (SpO2 ) via oxygen supplementation results to ANS function improvement, during steady state submaximal exercise. Methods: This is a secondary analysis of a single‐blind, randomized, placebo‐controlled, cross‐over trial, including 12 IPF patients, with isolated exertional desaturation. Following a maximal cardiopulmonary test, participants underwent two submaximal steady state tests during which they received either supplementary oxygen or medical air. Continuous beat‐to‐beat blood pressure measurements were recorded (Finapres Medical Systems, Amsterdam, The Netherlands). Autonomic function was assessed non‐invasively by heart rate variability (HRV); root mean square of successive differences (RMSSD) and standard‐deviation‐Poincare‐plot (SD1) were used as indices of parasympathetic output. Entropy and detrended fluctuation analysis (DFA) were also used. Results: During rest, oxygen supplementation did not significantly alter RMSSD and SD1. During exercise, subjects presented no significant alterations compared with baseline, in most HRV indices examined. There was no improvement of this behavior with O2 ‐supplementation. Approximate‐entropy increased during exercise, with no differences between protocols. Conclusions: IPF patients presented an inadequate adaptive response of their ANS to exercise and recovery. Although oxygen supplementation significantly prolonged exercise duration and prevented the substantial exertional desaturation, the blunted vagal response to steady‐state exercise in these patients was not improved, suggesting that acute oxygen supplementation does not sufficiently improve ANS dysfunction in these patients.